Focused parathyroidectomy without intraoperative parathormone testing is safe after pre-operative localization with 18F-Fluorocholine PET/CT. Issue 1 (January 2017) - Hocevar, M.; Lezaic, L.; Rep, S.; Zaletel, K.; Kocjan, T.; Sever, M.J.; Zgajnar, J.; Peric, B.
Abstract: A focused surgical approach based on pre-operative localization replaced the classical four-gland exploration in patients with primary hyperparathyroidism (PHP). Sestamibi scanning and ultrasound are most often used localization modalities with reported sensitivity of 54–100% for identification of single gland disease. The aim of this study was to analyze the results of pre-operative localization with 18 F-Fluorocholine PET/CT (FCh-PET) in patients with PHP. A retrospective review of 151 patients with PHP who underwent surgery after pre-operative localization with FCh-PET was performed. Only a focused parathyroidectomy without ioPTH testing had been done in patients with single adenoma on FCh-PET. Primary outcome was operative failure, defined as persistent PHP. According to pre-operative FCh-PET 126 (83, 4%) patients had single adenoma, 22 (14, 5%) multiglandular disease and the test was negative in only two patients. Intraoperative failure experienced 4/126 patients (3, 3%) with single adenoma. Removed parathyroid glands were normal in three and hyperplastic in one patient with intraoperative failure. A limited bilateral neck exploration with ioPTH testing was used in 14/22 patients with double adenoma and a classical four-gland exploration without ioPTH testing was used in 8/22 patients with more than two pathological glands according to pre-operative FCh-PET. Intraoperative failure experienced 2/22 patients (9, 1%). In two patients with negative FCh-PET a classical four-gland exploration without ioPTH testing was used and one experienced intraoperative failure. A preoperative localization with FCh-PET is a reliable test in patients with PHP. Patients with a single adenoma on FCh-PET can safely undergo a focused parathyroidectomy without ioPTH testing.